2017
DOI: 10.1016/j.ijid.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal colonization or infection with extended-spectrum beta-lactamase-producing Enterobacteriaceae in Africa: A systematic review and meta-analysis

Abstract: The prevalence of colonization and/or infection with ESBL-E in pregnant and post-partum women in Africa exceeds that reported from high- and middle-income settings, representing a risk for subsequent neonatal colonization and/or infection with ESBL-E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
(59 reference statements)
5
36
0
Order By: Relevance
“…There was high variability regarding the prevalence of ESBL‐P Enterobacteriaceae in different geographic regions as the highest rates were seen in Africa (point prevalence of 45%) and India (point prevalence of 33%) and the lowest ones belonged to North America (3%, although only two studies were found from this area) and Europe (5%). In a previous systematic review performed on studies from African countries, the authors reported a pooled prevalence of infection/colonisation by ESBL pathogens in pregnancy/postpartum period as 17%. It should be noted that, here, we did not include colonised mothers and confined the inclusion criteria to those diagnosed with symptomatic UTI/AB by urine culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was high variability regarding the prevalence of ESBL‐P Enterobacteriaceae in different geographic regions as the highest rates were seen in Africa (point prevalence of 45%) and India (point prevalence of 33%) and the lowest ones belonged to North America (3%, although only two studies were found from this area) and Europe (5%). In a previous systematic review performed on studies from African countries, the authors reported a pooled prevalence of infection/colonisation by ESBL pathogens in pregnancy/postpartum period as 17%. It should be noted that, here, we did not include colonised mothers and confined the inclusion criteria to those diagnosed with symptomatic UTI/AB by urine culture.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous systematic review and meta‐analysis studies have been conducted regarding the prevalence of ESBL‐P Enterobacteriaceae during pregnancy. In a systematic review confined to primary studies from Africa, the authors reported the pooled prevalence of maternal colonisation/infection with ESBL‐P Enterobacteriaceae as 17%. The other systematic review determined maternal colonisation with these organisms as 8% (95% CI, 5%‐10%) .…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in the first three days of life and usually transmitted from mother to baby during delivery [1]. e infection may be also transmitted vertically when the amniotic membrane ruptures or prior to the onset of labor causing intra amniotic infection [1,2]. e organisms most frequently associated with EOS are Streptococcus agalactiae and Escherichia coli [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…e infection may be also transmitted vertically when the amniotic membrane ruptures or prior to the onset of labor causing intra amniotic infection [1,2]. e organisms most frequently associated with EOS are Streptococcus agalactiae and Escherichia coli [1,2]. e latter accounts for about 24% of all EOS; 81% of cases occurring in preterm infants [1].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the proportion of pregnant women colonized by ESBL-E in the urinary tract ranges from 2.0 to 75%, the highest percentage found in developing countries [19,20]. In Africa, a high proportion above 70% is seen in sub-Saharan countries due to extensive antibiotic use in agriculture, veterinary, and human health centers [14,21]. In Tanzania, the proportion of ESBL-E to urinary isolates in pregnant women ranges between 18.8 and 45.2% [22].…”
Section: Introductionmentioning
confidence: 99%